2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00755
|View full text |Cite
|
Sign up to set email alerts
|

Few-Shot Image Recognition by Predicting Parameters from Activations

Abstract: In this paper, we are interested in the few-shot learning problem. In particular, we focus on a challenging scenario where the number of categories is large and the number of examples per novel category is very limited, e.g. 1, 2, or 3. Motivated by the close relationship between the parameters and the activations in a neural network associated with the same category, we propose a novel method that can adapt a pre-trained neural network to novel categories by directly predicting the parameters from the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
360
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 497 publications
(377 citation statements)
references
References 18 publications
0
360
0
Order By: Relevance
“…Few-shot learning. There is a broad array of few-shot learning approaches, including, among many: gradient descent-based approaches [1,11,38,44], which learn how to rapidly adapt a model to a given few-shot recognition task via a small number of gradient descent iterations; metric learning based approaches that learn a distance metric be-tween a query, i.e., test image, and a set of support images, i.e., training images, of a few-shot task [26,52,54,56,58]; methods learning to map a test example to a class label by accessing memory modules that store training examples for that task [12,25,34,37,49]; approaches that learn how to generate the weights of a classifier [13,16,42,43] or of a multi-layer neural network [3,18,19,57] for the new classes given the few available training data for each of them; methods that "hallucinate" additional examples of a class from a reduced amount of data [20,56].…”
Section: Related Workmentioning
confidence: 99%
“…Few-shot learning. There is a broad array of few-shot learning approaches, including, among many: gradient descent-based approaches [1,11,38,44], which learn how to rapidly adapt a model to a given few-shot recognition task via a small number of gradient descent iterations; metric learning based approaches that learn a distance metric be-tween a query, i.e., test image, and a set of support images, i.e., training images, of a few-shot task [26,52,54,56,58]; methods learning to map a test example to a class label by accessing memory modules that store training examples for that task [12,25,34,37,49]; approaches that learn how to generate the weights of a classifier [13,16,42,43] or of a multi-layer neural network [3,18,19,57] for the new classes given the few available training data for each of them; methods that "hallucinate" additional examples of a class from a reduced amount of data [20,56].…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results on miniImageNet are shown in Table 1, where we can see that our model achieves state-of-the-art performance with Con-vNet backbone and competitive results with ResNet architecture. We re-implement ProtoNet as our baseline with the simple pre-train strategy proposed by [23], and achieve better performance than previously reported ones in [29]. Taking ConvNet as an example, we get 51.68% and 68.71% for 5-way 1-shot and 5-way 5-shot respectively, which are slightly better than 49.42% and 68.20% in [29].…”
Section: Few-shot Learning Resultsmentioning
confidence: 73%
“…All backbone networks are optimized via SGD by Adam [13] end-to-end on DGX-1. Follow the strategy in [23,26], we pre-train the ConvNet to classify all seen classes and utilizing the optimal weights for model initialization, and we train ResNet from scratch for simplicity. Moreover, We perform TIM strategy in all experiments and set l = 0.5 and h = 1.0 for U(l, h).…”
Section: Experimental Settingsmentioning
confidence: 99%
“…It is observed that our CTM method compares favorably against most methods by a large margin, not limited to the metric-based methods but also compared with the optimization-based methods. For example, under the 5way 1-shot setting, the performance is 62.05% vs 59.60% [27], and 64.78% vs 59.91% [23] on the two benchmarks miniImageNet and tieredImageNet, respectively.…”
Section: Comparison Beyond Metric-based Approachesmentioning
confidence: 99%